Precautions Prior to the Treatment in Oraland Maxillofacia Surgery in the Reopening Period during COVID-19 Pandemic - DOĞANAY, ÖZGE; DOĞANAY, Özge; DOLANMAZ, DOĞAN; DOLANMAZ, DOĞAN (My University, 2021)
Oral and maxillofacial surgery is correlated with a high risk of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) transmission. To assist our colleagues under physical and psychological burden by using the current literature data and considering the recommendations of the Ministry of Health Science board decisions, -The American Association of Oral and Maxillofacial Surgeons, American Dental Association and Centers for Disease Control and Prevention, this literature review has been prepared in order to organize elective surgeries. Interventions should be planned after evaluating both the logistic conditions of the institution and the situation during the pandemic before per forming elective surgery. In order to save resources and to avoid unnecessary exposure to infected patients, there is the need to schedule interventions depending on their priority, In general, Emergency procedures do not allow any delay. In elective surgeries, risk assessments of both the patient and the surgical procedure is left to the surgeon. Inpatient and outpatient units have to he organized in such a way that the risk of cross-infection among patients is reduced to a minimum. Active Coronavirus disease-19 (COVID-19) patients should he treated in the operating room with negative pressure, and aerosol formation must be reduced to a minimum, During reopening period, treatments may he applied in cans whew appropriate conditions arc provided and recommendations for patient and physician safety are taken.
Keywords: COVID-19 pandemic; oral and maxillofacial surgery; personal protective equipment; reopening; elective treatments; protective measures